L'augoisse derrière le masque grinçant: Salacrou et le théâtre de l'humour noir - Labendz, Thérèse Eliane Yvonne (My University, 1971)
Salacrou's black humour, one of the most important characteristics of his theatrer will be discussed in this thesis.
Keywords: Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures